Productivity formation of maize hybrids depending on plant density in the conditions of Left-Bank Forest-Steppe - Mishchenko, O.; Hanhur, V.; Danilenko, Ye. (Scientific Progress & Innovations, 2024)
Maize (Zea mays L.) has a fairly wide range of uses, in particular, grain (production of flour and groats), fodder (production of mixed feed and silage), and technical (production of starch, bioethanol, and biogas). This favorably distinguishes it among the most important agricultural plants and gives it significant advantages over other field crops. According to the average two-year (2022–2023) research results, it was found that in the conditions of the Left-Bank Forest-Steppe of Ukraine, it is most expedient in growing an early-maturing hybrid of corn LG Jackline with a seeding rate 55 thousand pcs. ha-1, which contributes to the production of the highest grain yield (9.37 t/ha). Increasing the sowing rate to 60 and 65 thousand pcs. ha-1 of germinating seeds is not advisable due to the lower level of productivity compared to the previous sowing rate and an increase in production costs for seeds by 9.1–18.2 %. In this case, the grain yield was 12.13 t/ha, which increased by 1.5 and 5.8% compared to the sowing rate of 60 and 55 thousand pcs. ha-1 of germinating seeds, respectively. It was found that the most effective was the use of microfertilizer Maize Boost (2.0 l/ha) or its mixture with the growth stimulator Biotrak (1.0 l/ha) for foliar application of corn fields at the phase of 4–8 leaves. The grain yield increase of the hybrids LG Jackline and LG 31305 compared to the control (spraying with water) was 0.45 and 0.49 and 0.18 and 0.38 t/ha, respectively, or 5.0 and 5.4 and 1.6 and 3.3 %. In the variant where foliar fertilization of corn fields was applied with Gramitrel (2.0 l/ha), there was a tendency to increase the grain productivity of maize hybrids LG Jackline and LG 31305 compared to the control variant, but the difference in yield was not significant. It was found that the different seeding rates and biotype of the hybrid had no significant effect on the moisture content of corn grain before harvesting. In the early-ripening hybrid LG Jackline, it was in the range of 20.1–20.4 %, and in the mid-early hybrid LG 31305 – 19.9–20.3 %.